Kinetic of the thermal decomposition of disubstituted tetroxanes - Bordón, Alexander Germán (2016)
The thermal decomposition of diphenyl diperoxide (DFT) and dibutanal diperoxide (DPG) were investigated over the temperature range 130 to 166°C. They were found to be first order with a high degree of conversion (60%). Arrhenius parameters were calculated: activation energy, 108 kJ mol-1 and pre-exponential factor, 6.5 109 s -1 for DFT and 80.8 kJ mol-1 and pre-exponential factor, 1.8 109 s - 1 for DPG. The principle decomposition products were aldehyde (about 1.9 mole per mole DFT and 2.0 mole per mole DPG) and oxygen molecule. All observations were interpreted in terms of decomposition pathways initiated by O-O homolysis. The corresponding activation parameters for the reaction of DFT in methanol (ΔH0# = 103.8 ± 3.3 kJ mol-1 ; ΔS0# = -69.9 ± 7.5 J mol-1 K -1 ; ΔG0# = 133.1 ± 3.3 kJ mol-1) were compared with values obtained for PDG thermolysis in the same solvents (ΔH0# = 75.4 ± 2.9 kJ mol-1 ; ΔS0# = -189.2 ± 2.5 J mol-1 K -1 ; ΔG0# = 157.4 ± 2.9 kJ mol-1). Furthermore, the pertinent substituent effect on the peroxidic bond strength of those molecules in solution was evaluated.